Factors Associated with Not Drinking Alcoholic Beverages in Dependent Individuals on Recovery - Linda Azucena Rodríguez Puente; Fani Villa Rivas; Eva Kerena Hernández Martínez; Raúl Adrián Castillo Vargas; Dafne Astrid Gómez Melasio; Edna Idalia Paulina Navarro Oliva (Universidad de Antioquia, 2018)
Objective This work sought to determine the association between personal factors and not drinking alcoholic beverages in alcohol-dependent individuals on recovery process. Methods This was a cross-sectional quantitative study. The sample was comprised by 119 adult belonging to 50 Alcoholics Anonymous groups in Saltillo, Coahuila (Mexico). The sampling was simple random, by conglomerates (AA groups). To gather the information, a Personal Data Card was used along with a history on alcohol consumption and the instruments Scale on Social Readjustment Classification, Spiritual Perspective Scale, Schwartz Values Survey, and the Alcohol Use Disorders Identification Test (AUDIT). Results The time without alcohol consumption was related positively with age (r=0.59) and spirituality (r=0.29) and negatively with stressful events (r=-0.31). The Multiple Linear Regression Model explained 32.5% of the variance, with age being the variable remaining in the model and which affected not drinking alcoholic beverages. Conclusion Values and spirituality favor not drinking alcoholic beverages in individuals in the process of recovering from the dependence, while exposure to stressful events increases vulnerability to alcohol consumption.   How to cite this article: Rodríguez LA, Villa F, Hernández EK, Castillo RA, Gómez DA, Navarro EIP. Factors Associated to Not Drinking Alcoholic Beverages in Dependent Individuals on Recovery. Invest. Educ. Enferm. 2018; 36(3):e07.